Peningkatan Kesadaran Ekologis Dan Pemecahan Masalah Melalui Pembelajaran Autentik Interdisipliner Dengan Pemanfaatan Sungai Sebagai Sumber Belajar - Novianti, Novianti; Nuri, Bulan; Hanum, Erlia; Khaulah, Siti; Yuhafliza, Yuhafliza (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem of low ecological awareness among students and the community and the limited application of contextual learning in schools are challenges in 21st century education that demands concern for the environment and critical thinking skills. This community service activity aims to increase ecological awareness and problem-solving skills through the application of interdisciplinary authentic learning by utilizing rivers as a learning resource. The method of implementing the activity uses the Participatory Action Research (PAR) approach which involves the active participation of students, community service teams and the community in all stages of the activity, starting from problem identification, planning, action implementation, reflection, to evaluation. The activity begins with observation and focus group discussions to identify river problems. Furthermore, teacher training is carried out on interdisciplinary authentic learning, mentoring in the development of teaching tools, and the implementation of project-based learning in the river environment. The results of the activity show an increase in teacher understanding in designing contextual learning, active involvement of students in collecting data and compiling environmental solutions, and the emergence of community awareness of the importance of river conservation. Joint reflection confirms that learning based on real problems is able to build concern, collaboration, and ecological literacy in various parties. From this activity, it was concluded that rivers as an effective learning resource are used to build meaningful learning, strengthen 21st century skills, and encourage sustainable environmental action through a community-based collaborative approach.